THE PSYCHOLOGICAL IMPACT OF ACADEMIC PROCRASTINATION ON PERSONALITY - Turanova , Nihola (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article theoretically and practically analyzes the impact of academic procrastination on individual psychology. During the research, the essence of the concept of procrastination, the causes of its occurrence, and the characteristics of its manifestation among students were highlighted. In addition, the negative impact of academic procrastination on an individual’s emotional state, motivation, self-confidence, and effectiveness of educational activity was studied. According to the results of the study, procrastination was identified as one of the factors that increase anxiety, stress, emotional tension, and psychological instability among students.